The effect of capital structure and corruption on economic growth: Empirical evidence from Nigeria - Olabisi, Olabode Eric; Ololade, Babatunde Moses; Akande, Adesola Adebayo; Abass, Kehinde Babatunde (Asian Journal of Empirical Research, 2023)
Corruption thrives in an environment characterized by weak institutions that couldn’t enforce economic discipline to engender societal trust among market participants. It affects economic transactions relating to raising capital between corporate managers, shareholders, and members of the public. The extent of the effect of corruption and capital structure on economic growth in emerging economies has not been extensively investigated. This study examined the effect of capital structure and corruption on the economic growth of Nigeria between 2010-2021. The panel quantile regression technique was employed. To check the robustness of the panel quantile results, the technique of ordinary least squares estimations was used. The results show that a 1% increase in the corruption level and inflation reduces the Nigerian economic growth rate by 1.5781% and 0.0162% in the 20th percentile respectively. The significant negative impacts of corruption and inflation are consistent across all the percentiles. However, variables of the capital structure have no impact on the direction of Nigerian economic growth.